LeXmart: A Smart Tool for Lexicographers - Simões, Alberto (2019)
The digital era has brought some challenges to lexicographers, but it has also brought new opportunities as part of the rise of information technology and, more recently, the emergence of digital humanities. This paper provides a description of LeXmart, the framework that supports the digital development of the Portuguese Academy of Sciences Dictionary. LeXmart is a smart tool framework to support lexicographers’ work that offers different types of tools, ranging from a structural editor to a set of validation tools. Given that the dictionary is stored in eXist-DB, LeXmart is developed on top of its ecosystem, using W3C standard languages, and offering default functionalities offered by eXist-DB, namely a RESTful API.